A visualização de objetos geométricos por alunos cegos: um estudo sob a ótica de Duval - Mello, Elisabete Marcon (2015)
This thesis aimed to investigate how blind students visualize geometric objects, based on the Theory of Semiotics Representation, Vision and View Registers of Raymond Duval. Checking the official documents that determine the course of education, we found that they establish that children and young people with special educational needs must have access to schools, preferably in the regular school system, which must be suitable to them, both materially and educationally. So, we performed a case study in a public school in the city of Santo André, São Paulo, which has blind students attending ordinary classrooms. Through interviews, we investigated how congenitally blind students recognize and work with representations of geometric objects and what are the possibilities of these students create their own representations on paper. We found that the interviewed students identified flat geometric figures embossed on paper, recognizing their forms, but didn t recognize the geometric solids representations in perspective, because the outline of these objects does not match with their outline on paper. We note the need to teach how to visualize, it is necessary that the blind students learn how to identify the represented object in each representation, this recognition is not automatic but it can be learned. We noted that the order of perception by touching is different when the blind student has a concrete object in his hands and when it has a representation of this object embossed on paper. When the blind student has a concrete object in his hands, and this object is familiar to him, he recognizes the entire object without the need to observe the parts, but when the representation is embossed on paper, even if the student knows the represented object, he visualizes the parts first and then the entire object. In the interviews, we witnessed times when the students reached the perceptual, operative and discursive apprehensions, despite having a very limited repertoire of geometric terms. One of the students operated the dimensional deconstruction of the forms and could "see" mathematically, as mentioned by Duval (2011). None of the students we interviewed had ever built or designed geometric figures in a way that after they could recognize them, so the sequential apprehension that aims at the construction of geometric figures was not observed during our investigation. Seeking to fill this gap, we propose the creation of the Drawing on Positive Relief Clipboard, with which a blind student has the possibility to design and feel the design embossed on paper